Peningkatan Hasil Belajar dan Motivasi Belajar Siswa melalui Pendekatan Behavior Modification - Suminah Suminah; Imam Gunawan; Sri Murdiyah (Faculty of Education Universitas Negeri Malang, 2018)
Abstract: The purpose of this research is to improve learning achievement and student learning motivation through behavior modification approach in Class V Elementary School Laboratory State University of Malang (UM) Blitar City. This research was conducted using classroom action research method. This study was conducted with two cycles. Data collection techniques used in this study is tests and observations. Data were analyzed with descriptive statistics, i.e. calculating the mean and standard deviation. Furthermore, by using the formula stanfive data formulated with the frequency distribution table. Data analysis is by comparing the results of the scores obtained from Cycle I and Cycle II (data learning achievement and student learning motivation). Data analysis is analysis of variance of paired-samples t test formula with SPSS PASW Statistics 18. The result of research are: (1) student learning achievement through behavior modification approach included in good enough category; (2) the level of student’s learning motivation through behavior modification approach included in high enough category; and (3) there is improvement of learning achievement and student’s learning motivation through behavior modification approach in Class V Elementary School Laboratory of State University of Malang (UM) Blitar City. Abstrak: Tujuan penelitian ini adalah untuk meningkatkan hasil belajar dan motivasi belajar siswa melalui pendekatan behavior modification di Kelas V SD Laboratorium Universitas Negeri Malang (UM) Kota Blitar. Penelitian ini dilaksanakan dengan menggunakan metode penelitian tindakan kelas. Penelitian ini dilaksanakan dengan dua siklus. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah tes dan observasi. Data dianalisis dengan statistik deskriptif, yakni menghitung rerata dan deviasi standar. Selanjutnya dengan menggunakan rumus formula stanfive data disusun dengan tabel distribusi frekuensi. Analisis data yakni dengan membandingkan hasil skor yang diperoleh dari Siklus I dan Siklus II (data hasil belajar dan motivasi belajar siswa). Analisis data adalah analisis varians formula paired-samples t test dengan bantuan SPSS PASW Statistics 18. Hasil penelitian adalah: (1) tingkat hasil belajar siswa melalui pendekatan behavior modification termasuk dalam kategori cukup baik; (2) tingkat motivasi belajar siswa melalui pendekatan behavior modification termasuk dalam kategori cukup tinggi; dan (3) ada peningkatan hasil belajar dan motivasi belajar siswa melalui pendekatan behavior modification di Kelas V SD Laboratorium Universitas Negeri Malang (UM) Kota Blitar.